PENGARUH PUPUK KANDANG AYAM TERHADAP SERAPAN KALIUM (K) TANAMAN SELADA (LACTUCA SATIVA. L) PADA ENTISOLS LEMBAH PALU - Siti Ramadan; Muh. Basir; Imam Wahyudi (Universitas Tadulako, 2018)
This study aimed to determine the effect of chicken manure on potassium uptake in lettuce (Lactuca Sativa L). The results of this research are expected to generate information useful for developing lettuce (Lactuca Sativa L.) cultivation inEntisolsLembahPalu. The preliminary soil physical analysis showed that soil bulk density was 1.45 gcm-1 with 32.35% porosity,soil permeability was 2.94cmh-1, and soil texture was loam. Whilst the soil chemical characteristics indicated that soil pH was 6.57,exchangeable Al was 0.19 cmol (+) kg-1, exchangeable H was 0.79 cmol (+) kg-1, C-organic was 1.75%, N-total was 0.06%, K2O was 26.30 mg 100g-1, P2O5was 21.51 mg 100g-1, CEC was 14.53cmol (+) kg-1, K was 0.47 cmol (+) kg-1, Na was 0.01 cmol (+) kg-1, and Cawas 8.64 cmol (+) kg-1.These results suggests that the soil has not yet developed with its characteristics mostly similar to its parent materials. Adding chicken manure to this soil increased Lettuce K uptake with increasing rates of the manure. Keywords: Chicken manure, lettuce, and potassium uptake.